Employing in vitro metabolism to guide design of F-labelled PET probes of novel α-synuclein binding bifunctional compounds. (3rd August 2021) - Nwabufo, Chukwunonso K.; Aigbogun, Omozojie P.; Allen, Kevin J.H; Owens, Madeline N.; Lee, Jeremy S.; Phenix, Christopher P.; Krol, Ed S.
Abstract: A challenge in the development of novel 18 F-labelled positron emission tomography (PET) imaging probes is identification of metabolically stable sites to incorporate the 18 F radioisotope. Metabolic loss of 18 F from PET probes in vivo can lead to misleading biodistribution data as displaced 18 F can accumulate in various tissues. In this study we report on in vitro hepatic microsomal metabolism of novel caffeine containing bifunctional compounds (C8 -6-I, C8 -6-N, C8 -6-C8 ) that can prevent in vitro aggregation of α-synuclein, which is associated with the pathophysiology of Parkinson's disease. The metabolic profile obtained guided us to synthesize stable isotope 19 F-labelled analogues in which the fluorine was introduced at the metabolically stable N7 of the caffeine moiety. An in vitro hepatic microsomal metabolism study of the 19 F-labelled analogues resulted in similar metabolites to the unlabelled compounds and demonstrated that the fluorine was metabolically stable, suggesting that these analogues are appropriate PET imaging probes. This straightforward in vitro strategy is valuable for avoiding costly stability failures when designing radiolabelled compounds for PET imaging.